Behaviour of sheep in three different types of paddock in karst region of Slovenia - Bojkovski, Danijela; Stuhec, Ivan; Kompan, Dragomir (Acta Agraria Kaposváriensis, 2006)
Forty sheep and ten goats were reared on three different types of paddock (grass paddock, woody, and partly woody paddock). Behaviour of the ten marked sheep was observed during the time of day light (between 5 a.m. and 9 p.m.). Frequency of the following activities was monitored: grazing, drinking, salt consumption, aggressive behaviour, comfort behaviour and resting (in lying position, in standing position and resting in the flock). On average, the animals were grazing 10.5 hours per day. Circadian rhythm of grazing was different, depending on the type of paddock and on average daily temperature. Drinking frequency was very low. On average, each animal drank 0.99 times per day. Salt consumption, frequency of aggressive behaviour and comfort behaviour were most frequent in woody paddock. Two types of resting (in lying position and resting in the flock) had almost the same percent of the total resting time (46âˆ’47%), while the third type of resting (in standing position) had the lowest percent in all three types of paddock (about 7%).